Komuniciranje je moč - Hardt, Hanno (Javnost (Ljubljana), 2004)
This short essay describes the contemporary process of communication in (American) society and its relations to power in the guise of democratic practice. It offers a suggestive rather than exhaustive critique and argues for a turn of communication studies to a social and cultural critique of power, not only to enhance its theoretical position and validate its political standing in society, but to suggest revolutionary alternatives to present conceptions of (mass) communication that reinvent a democratic vision of communication in society.
Keywords: komuniciranje; communication; mass media; množični mediji; sociologija komunikacij; javnost; democracy; demokracija; svoboda; nadzor